2015
DOI: 10.1051/mbcb/2015003
|View full text |Cite
|
Sign up to set email alerts
|

Tori et exostoses multiples : présentation d’un cas et revue de la littérature

Abstract: Résumé -Introduction :Les exostoses et les tori sont des excroissances osseuses bénignes ayant différentes localisations. Les facteurs intervenant dans leur apparition sont encore discutés. Ces excroissances sont asymptomatiques, mais elles peuvent parfois occasionner différentes gênes. De ce fait, leur exérèse n'est que rarement nécessaire. Observation : Il s'agit d'une femme de 58 ans présentant des exostoses et des tori maxillaires et mandibulaires volumineux, associés à un bruxisme aggravé ayant entraîné d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The average prevalence of palatal tori seems to be 20-40% with significant topographical disparities. Most authors have observed a predominance of palatal tori in women as well as a larger average size [1][2][3][4].…”
Section: Epidemiologymentioning
confidence: 99%
See 4 more Smart Citations
“…The average prevalence of palatal tori seems to be 20-40% with significant topographical disparities. Most authors have observed a predominance of palatal tori in women as well as a larger average size [1][2][3][4].…”
Section: Epidemiologymentioning
confidence: 99%
“…Palatal tori are mostly asymptomatic, which is why they usually go unnoticed, and characterized by a fortuitous discovery during a routine examination by the practitioner or by the patients themselves. The diagnosis of palatal torus is clinical, but radiographic and pathological examinations may sometimes be useful [1,2].…”
Section: Clinical and Paraclinical Diagnosismentioning
confidence: 99%
See 3 more Smart Citations